Prognostic Indicators in Cats with Hypertrophic Cardiomyopathy. (17th October 2013) - Payne, J.R.; Borgeat, K.; Connolly, D.J.; Boswood, A.; Dennis, S.; Wagner, T.; Menaut, P.; Maerz, I.; Evans, D.; Simons, V.E.; Brodbelt, D.C.; Luis Fuentes, V.
<x xml:space="preserve">Abstract</x> Background Left atrial (LA) enlargement, congestive heart failure (CHF), and aortic thromboembolism (ATE) are associated with decreased survival in cats with hypertrophic cardiomyopathy (HCM), but the prognostic value of echocardiographic variables has not been well characterized. Hypothesis/Objectives We hypothesized that LA echocardiographic variables and assessment of left ventricular (LV) diastolic and systolic function would have prognostic value in cats with HCM. Animals Two hundred eighty‐two cats diagnosed with HCM. Methods Clinical and echocardiographic records of affected cats seen at the Royal Veterinary College from 2004 to 2009 were retrospectively analyzed. Only cats with echocardiographic confirmation of LV diastolic wall thickness ≥6 mm were included. Outcomes were obtained from clinical records or referring veterinarians and owners. Results Deaths occurred in 164 cats, of which 107 were believed to have been cardiac deaths. Univariable predictors of an increased risk of cardiac death included older age, absence of a murmur, presence of a gallop sound or arrhythmia, presentation with either CHF or ATE, extreme LV hypertrophy (≥9.0 mm), LV fractional shortening (FS%) ≤30%, regional wall hypokinesis, increased left atrial size, decreased left atrial function, spontaneous echo‐contrast/thrombus or both, absence of left ventricular outflow tract obstruction, and a restrictive diastolic filling pattern. Cox's proportional hazard analysis identified LA dysfunction, low LV systolic function, and extreme LV hypertrophy as independent predictors of decreased cardiac survival time. Conclusions and Clinical Importance Echocardiographic measurement of LA function, extreme LV hypertrophy, and LV systolic function provides important prognostic information in cats with HCM.